Template-free assembly of 2D-electrolytes into nanofibres. (August 2021) - Marangoni, V.S.; Costa, M.C.F.; Ng, P.R.; Nguyen, H.T.L.; Trushin, M.; Carvalho, A.; Zhao, X.; Pennycook, S.J.; Donato, R.K.; Castro Neto, A.H.
Abstract: The assembly of graphene-based materials into nanofibres is of intense technological interest for numerous applications ranging from tissue engineering and drug delivery to fuel cells and space elevators. We demonstrate a composite nanofibre synthesis process using functionalised graphene structures in liquid medium (two-dimensional [2D] electrolytes) as building blocks. The approach consists in simultaneous scrolling and reacting 2D electrolytes, leading to a dimensional reduction of 2D materials into one-dimensional nanostructures. The spontaneous self-assembly and cross-linking processes allow to produce nanofibres without the need of fibrillation techniques, such as wet-spinning or external templates. Graphical abstract: Image 1 Highlights: Spontaneous 2D to 1D morphology transition of 2D electrolytes. 2D electrolytes as building blocks to nanofibres. Simultaneous scrolling and self-assembly of functionalised 2D materials into nanofibres. Nanofibres with extremely high aspect ratio. Hybrid nanofibre formation in water medium.